DESIGN AND CONSTRUCTION OF WORK OBJECTS USING A MAGNETIC VENUE ON A DRILL MACHINE - Angky Purwa Tarozzi; Asep Rachmat; Eidelweis Dewi Jannati (Jurnal Mekanika dan Manufaktur, 2022)
The development of science and technology and along with advances in the field of industry, especially in the field of machinery, various tools were created to simplify and increase human comfort in fulfilling their needs. The workpiece gripping mechanism on the sitting drill machine works by being controlled manually using a control lever, making it difficult for the operator to operate and making the processing time long. The author will conduct research on the design of workpiece gripping tools using a magnetic vise on a drilling machine. It is hoped that the design of this magnetic vise can reduce the work of an operator and can shorten the time of installing the workpiece so that it can increase the work productivity of the drilling machine, reduce operating costs and increase the work safety of an operator. From the results of the analysis of the design of the Magnetic Vise designer, it can be concluded that the circular magnetic field around the wire is 8100π x 10-4 Tesla, Resultant of Magnetic Induction in Parallel Wire B1 = 18 x 10-5 Tesla and B2 = 10.8 x 10 -5 Tesla, Resultant magnitude of magnetic induction Bp = 28.8 x 10-5 Tesla. The solenoid is a coilshaped wire with fairly tight turns and has a length of = 360 cm with a number of turns = 150, the magnitude of the magnetic induction at the end of the solenoid is different from the magnitude of the magnetic induction at the center of the solenoid. The magnitude of the magnetic induction at the center of the solenoid is 45 x 10-5 Tesla. larger than the solenoid tip by 11.25 x 10-5 Tesla.